(untitled) (Acta Scientiarum. Biological Sciences, 2013)
The environment quality of an industrial district on the river Pará, Amazon estuary, Brazil, based on the assessment of histological alterations and on the determination of catalase activity of the hepatic tissue of two fish species, Plagioscion squamossissimus and Lithodoras dorsalis, is provided. Histopathological changes were evaluated semi-quantitatively and qualitatively. Mean Assessment Values (MAV) and Histological Alteration Index (HAI) of organ lesions were calculated for each zone under analysis, with different impact levels: Zone 1 (industrial district, with high contamination risk); Zone 2 (medium risk) and Zone 3 (minimum risk). Strong positive catalase activity and histopathological changes were reported in Zone 1. None of the specimens of either species captured in Zones 1 and 2 was healthy, whereas more than 60% of the specimens from Zone 3 presented healthy hepatic tissue. The principal alterations observed in the tissue of the two species included an increase in the number of Melanomacrophagous centers, fatty degeneration, inflammation, congestion, hepatitis and focal necrosis. The carnivorous P. squamosissimus presented higher levels of alteration than the herbivorous L. dorsalis. Results showed that local anthropogenic impacts were affecting the health of the two fish species under analysis.